Disseminated histoplasmosis (Histoplasma capsulatum) in a pet rabbit: case report and review of the literature. (January 2014) - Brandão, João; Woods, Samantha; Fowlkes, Natalie; Leissinger, Mary; Blair, Robert; Pucheu-Haston, Cherie; Johnson, James; Elster Phillips, Christina; Tully, Thomas
A 2.5-year-old intact male miniature lop rabbit ( Oryctolagus cuniculus ) was presented with multiple nodules surrounding the eyes, nose, mouth, and prepuce. Cytological evaluation of the periocular nodules revealed the presence of intracellular (within macrophages) and extracellular yeast organisms. The yeast organisms were approximately 3–5 µm in diameter, round to oval, with a thin clear capsule, and contained an eccentrically placed basophilic crescent-shaped nucleus. The clinical pathological interpretation was granulomatous inflammation with intralesional yeast of a morphology consistent with Histoplasma spp. The rabbit was treated with microsized griseofulvin (25 mg/kg, orally, once a day) for 12 days pending final cytological diagnosis of histoplasmosis. No significant improvement was noted during the treatment period, and humane euthanasia was performed. Postmortem examination revealed the presence of intracellular and extracellular yeast organisms in the small intestine, skin (antebrachium, perioral, palpebral, perianal, and pinnal), penis, penile urethra, rectum, axillary lymph node, and conjunctiva. Postmortem fungal culture yielded Histoplasma capsulatum . Based on clinical and postmortem findings, a definitive diagnosis of disseminated histoplasmosis was made. Disseminated histoplasmosis appears to be unreported in rabbits. Although the treatment used did not provide noticeable improvement, available information on histoplasmosis treatment in other species has been reviewed to provide useful information for future management of this condition in rabbits.